Comparative Genomics of Enterococci: Variation in Enterococcus faecalis, Clade Structure in E. faecium, and Defining Characteristics of E. gallinarum and E. casseliflavus - Kelli L. Palmer (American Society for Microbiology, 2012)
ABSTRACT The enterococci are Gram-positive lactic acid bacteria that inhabit the gastrointestinal tracts of diverse hosts. However, Enterococcus faecium and E. faecalis have emerged as leading causes of multidrug-resistant hospital-acquired infections. The mechanism by which a well-adapted commensal evolved into a hospital pathogen is poorly understood. In this study, we examined high-quality draft genome data for evidence of key events in the evolution of the leading causes of enterococcal infections, including E. faecalis, E. faecium, E. casseliflavus, and E. gallinarum. We characterized two clades within what is currently classified as E. faecium and identified traits characteristic of each, including variation in operons for cell wall carbohydrate and putative capsule biosynthesis. We examined the extent of recombination between the two E. faecium clades and identified two strains with mosaic genomes. We determined the underlying genetics for the defining characteristics of the motile enterococci E. casseliflavus and E. gallinarum. Further, we identified species-specific traits that could be used to advance the detection of medically relevant enterococci and their identification to the species level. IMPORTANCE The enterococci, in particular, vancomycin-resistant enterococci, have emerged as leading causes of multidrug-resistant hospital-acquired infections. In this study, we examined genome sequence data to define traits with the potential to influence host-microbe interactions and to identify sequences and biochemical functions that could form the basis for the rapid identification of enterococcal species or lineages of importance in clinical and environmental samples.